A Simple Approach to Modeling Rural and Urban District Heating - Brocklebank, Ian; Beck, Stephen B. M.; Styring, Peter (Frontiers in Energy Research, 2018)
If the UK wishes to decarbonize its heat supply, increased implementation of district heating is needed. Currently, district heating implementation is low, accounting for only 2% of the total UK heat supply. Low district heating implementation is mainly due to the high network installation costs, particularly in rural areas with low heat demand density. Current academic models of district heating are complicated, time consuming and require validation with primary network data. This paper aims to report on the building of a simple model that can, quickly and easily, assess the economic and environmental feasibility of any new district heating network. A primary aim of the model is to be simple enough for non-technical individuals to use. The focus of the paper is on the modeling of the local heat demand, investigating the applicability of the same modeling technique to case studies with differing population densities. Results showed that case study areas with smaller population densities had higher proportion of domestic customers, therefore the modeling process will need to be modified to ensure that domestic customers are not included in future heat demand assessments. Case study areas with smaller population densities had significantly longer pipe networks, which will affect later techno-economic modeling. Monte Carlo simulations highlighted errors in the data collection process, which was changed to improve the accuracy of counting and measuring the building sizes.